Associations of foot and ankle characteristics with knee symptoms and function in individuals with patellofemoral osteoarthritis - Jade M. Tan (Journal of Foot and Ankle Research, 2020)
Abstract Background Foot and ankle characteristics are associated with patellofemoral pain (PFP) and may also relate to patellofemoral osteoarthritis (PFOA). A greater understanding of these characteristics and PFOA, could help to identify effective targeted treatments. Objectives To determine whether foot and ankle characteristics are associated with knee symptoms and function in individuals with PFOA. Methods For this cross-sectional study we measured weightbearing ankle dorsiflexion range of motion, foot posture (via the Foot Posture Index [FPI]), and midfoot mobility (via the Foot Measurement Platform), and obtained patient-reported outcomes for knee symptoms and function (100 mm visual analogue scales, Anterior Knee Pain Scale [AKPS], Knee injury and Osteoarthritis Outcome Score, repeated single step-ups and double-leg sit-to-stand to knee pain onset). Pearson’s r with significance set at p < 0.05 was used to determine the association between foot and ankle charateristics, with knee symptoms and function, adjusting for age. Results 188 participants (126 [67%] women, mean [SD] age of 59.9 [7.1] years, BMI 29.3 [5.6] kg/m2) with symptomatic PFOA were included in this study. Lower weightbearing ankle dorsiflexion range of motion had a small significant association with higher average knee pain (partial r = − 0.272, p < 0.001) and maximum knee pain during stair ambulation (partial r = − 0.164, p = 0.028), and lower scores on the AKPS (indicative of greater disability; partial r = 0.151, p = 0.042). Higher FPI scores (indicating a more pronated foot posture) and greater midfoot mobility (foot mobility magnitude) were significantly associated with fewer repeated single step-ups (partial r = − 0.181, p = 0.023 and partial r = − 0.197, p = 0.009, respectively) and double-leg sit-to-stands (partial r = − 0.202, p = 0.022 and partial r = − 0.169, p = 0.045, respectively) to knee pain onset, although the magnitude of these relationships was small. The amount of variance in knee pain and disability explained by the foot and ankle characteristics was small (R2-squared 2 to 8%). Conclusions Lower weightbearing ankle dorsiflexion range of motion, a more pronated foot posture, and greater midfoot mobility demonstrated small associations with worse knee pain and greater disability in individuals with PFOA. Given the small magnitude of these relationships, it is unlikely that interventions aimed solely at addressing foot and ankle mobility will have substantial effects on knee symptoms and function in this population. Trial registration The RCT was prospectively registered on 15 March 2017 with the Australia and New Zealand Clinical Trials Registry ( ANZCTRN12617000385347 ).